Isolation and Identification of Coliform Bacteria in Street Food Products from the Pangandaran Coastal Area, Indonesia - Rizq Aaqilah Gusly; Malvin Albert; Diffa Amanda Iswhara; Jiang Lei; Yolani Syaputri (Research and Social Study Institute, 2026)
Background: The Pangandaran coastal tourism area, characterized by high visitor density, presents a significant risk for foodborne illness. Data from the West Java Provincial Health Office recorded diarrheal cases in Pangandaran Regency between 2016 and 2024 ranging from 8,003 to 11,789 cases per year, indicating persistent concerns regarding sanitation and food quality. Aims: This study aimed to evaluate the presence of coliform bacteria in street foods sold in the Pangandaran coastal tourism area through a comprehensive laboratory-based approach.Methods: Food samples were collected using purposive sampling. Analysis was performed through Total Coliform Count (TCC), coliform confirmation testing, Gram staining, and the IMViC test series.Results: TCC values in cilok (107 × 10² CFU/g) and pecel sayur (2,173 × 10² CFU/g) exceeded the established maximum limits. In contrast, sosis (47 × 10² CFU/g), siomay (35 × 10² CFU/g), and rujak buah (18 × 10² CFU/g) remained within acceptable limits. Bakwan, cakwe, cimol, and ketan kukus showed no colony growth. Gram staining, coliform confirmation, and IMViC tests confirmed the presence of Gram-negative bacteria in contaminated samples, with characteristics indicative of Escherichia coli based on morphological and biochemical profiles.Conclusion: Cilok and pecel sayur contained coliform contamination exceeding the maximum permissible limits, with isolates indicative of E. coli in several samples. Improvements in hygiene, sanitation, and food safety monitoring for street food vendors in the area are strongly recommended, alongside molecular confirmation for definitive species identification.